Corrosion of electrodeposited Sn in 0.01 M NaCl solution. A EQCM and EIS study. (1st June 2016) - Collazo, A.; Figueroa, R.; Nóvoa, X.R.; Pérez, C.
Graphical abstract: Highlights: The corrosion of electrodeposited tin occurs shows three OCP plateaux. CV, EIS and EQCM were employed as in-situ techniques to study Sn corrosion and electrodeposition. Abnormally high capacitance values are recorded at the beginning of the corrosion process. OCP plateaux are related to selective dissolution of specific crystal planes. Abstract: The corrosion kinetics of electroplated tin was studied in a chloride-containing aqueous solution by combination of Electrochemical Quartz Cristal Microbalance (EQCM), Electrochemical Impedance Spectroscopy (EIS) and Cyclic Voltammetry (CV). Three different Open Circuit Potential (OCP) plateaux can be observed during the corrosion process of the tin layer. The potentials of those plateaux correlate to anodic peaks observed in CV. EQCM data indicate that the corrosion rate varies from plateau to plateau. The EIS measurements show variable interfacial impedance during the corrosion tests, which has been correlated to the presence of two preferred orientations of tin crystals, as identified by XRD. The different orientations produce different morphologies of the tin layer. One of the morphologies corresponds to a large active surface and a high corrosion rate, while the other one is a smoother surface and shows a slower corrosion rate.